Common network coding condition and traffic matching supported network coding aware routing for wireless multihop network - Cuixiang Wang; Xing Shao; Zhi Gao; Chuanxin Zhao; Jun Gao (International Journal of Distributed Sensor Networks)
Network coding–based routing has been widely considered as a promising technology to improve the network throughput of wireless multihop network. However, existing network coding aware routings have the problem of failure decoding and usually neglect the transmission scheduling, which degrades the gain of network coding. In this article, a common network coding condition and traffic matching supported network coding aware routing is proposed for wireless multihop network. In this, common network coding condition is proposed to avoid the problem of failed decoding. In addition, traffic matching mechanism is presented to promote the occurrence of network coding. Besides, a coding and load aware routing metric, which jointly considers the network coding opportunity and node load, is designed to evaluate the discovered paths. Extensive simulations on NS2 demonstrate that CTNR increases the number of coding opportunities and network coding occurrence, and improves network throughput.